Factors associated with survival after allogeneic transplantation for myeloid neoplasms harboring TP53 mutations - Anmol Baranwal; Kimberly J. Langer; Vedavyas Gannamani; Danielle Rud; Alia Cibich; Caner Saygin; Mariam Nawas; Talha Badar; Mohamed A. Kharfan-Dabaja; Ernesto Ayala; Vivek Roy; James M. Foran; et al. (Blood Advances)
Abstract: Allogeneic hematopoietic stem cell transplant (alloHCT) is considered for all patients with myeloid neoplasms (MNs) harboring TP53 mutations (TP53mut). The aim of this international study across 7 transplant centers in the United States and Australia was to identify factors associated with improved post-alloHCT survival. Of 134 TP53mut MN cases who underwent alloHCT, 80% harbored complex karyotype; 94% of TP53 variants were localized to the DNA-binding domain (DBD). Most common comutations were ASXL1 (7%), TET2 (7%), and DNMT3A (6%). Median post-HCT survival was 1.03 years, and overall survival (OS) at 1 year, 2 years, and 3 years was 51.4%, 35.1%, and 25.1%, respectively. A total of 103 cases (76.9%) met the International Consensus Classification (ICC) criteria for MN with mutated TP53 (referred to as ICC-defined TP53mut MN hereafter). The 3-year OS of ICC-defined TP53mut was significantly shorter compared with that of other TP53mut MNs (3-year OS, 16.9% vs 54.9%; P = .002). ICC-defined TP53mut MNs was independently associated with inferior OS (hazard ratio [HR], 2.62; P = .019). The presence of non-DBD TP53mut only (HR, 3.40; P = .005), DNMT3A comutation (HR, 2.64; P = .016), and pre-alloHCT bone marrow blasts ≥5% (HR, 2.76; P = .006) was independently associated with inferior relapse-free survival (RFS), whereas melphalan-based conditioning was associated with superior RFS (HR, 0.52; P = .005). Combining these variables, we constructed a hierarchical model that stratified patients into low-, intermediate-, and high-risk categories with 1-year RFS of 81.3%, 31.3%, and 6.7%, respectively (P < .001). In conclusion, a subset of MN harboring TP53mut who have low blasts pre-alloHCT and received melphalan-based conditioning derived long-term benefit from alloHCT.